Electric vehicle industry sustainable development with a stakeholder engagement system - Cao, Jidi; Chen, Xin; Qiu, Rui; Hou, Shuhua (Technology in society, 2021)
Electric vehicles emerge as the possible strategy for decarbonization and green transportation due to social demand. Researchers have made multiple efforts and initiatives as the demand surge for sustainable development in the electric vehicle industry. This study analyzes the relevant research of the industry, thereby explores electric vehicle industry development trends with a scientometrics-based data evaluation system, where three key topics are detected: “Vehicle Exhaust Emissions”, “Climate Change”, and “Integration”. The results are visualized in the view of clusters, timeline, and time zone to explore the dynamic direction and future trends of the industry. Further trend detection and forward-looking analysis suggest the significance of stakeholders and their interconnection. In response to the significant challenges in sustainable development, this study proposes the stakeholder engagement system in a comprehensive perspective. The system firstly reveals the driving forces behind the industry development, that is how different motivation and strategies orientate the industry towards sustainability. Then, it furtherly analyzes the commitments and efforts needed from multiple stakeholders, through policy implications, leading factors on demand side, and technology innovation requirements on supply side. The stakeholder engagement system may contribute to stakeholder synergy and resource optimization hence for electric vehicle industry sustainable development and novel ideas to other relevant research fields. •Electric vehicle industry development trends are explored.•A stakeholder engagement system for industry sustainable development is established.•Integration strategies orientate the industry towards sustainable development.•Technology innovation requirement in supply is analyzed.